45 or 50 Gy, Which is the Optimal Radiotherapy Pelvic Dose in Locally Advanced Cervical Cancer in the Perspective of Reaching Magnetic Resonance Image-guided Adaptive Brachytherapy Planning Aims?. Issue 3 (March 2016) - Mazeron, R.; Petit, C.; Rivin, E.; Limkin, E.; Dumas, I.; Maroun, P.; Annede, P.; Martinetti, F.; Seisen, T.; Lefkopoulos, D.; Chargari, C.; Haie-Meder, C.
Abstract: Aims: In locally advanced cervical cancer, the dose delivered results from the sum of external beam radiotherapy and brachytherapy, and is limited by the surrounding organs at risk. The balance between both techniques influences the total dose delivered to the high-risk clinical target volume (HR-CTV). The aim of the present study was to compare the ability of reaching different planning aims after external beam radiotherapy pelvic doses of 45 Gy in 25 fractions or 50.4 Gy in 28 fractions, both considered as standard prescriptions. Materials and methods: The optimised plans of 120 patients treated with pelvic chemoradiation followed by magnetic resonance image-guided intracavitary brachytherapy were reviewed. The doses per pulse were calculated, and the number of pulses required to reach the planning aims, or a limiting dose constraint to organs at risk, was calculated. All doses were converted to 2-Gy equivalents. Three scenarios were applied consisting of different sets of planning aims: 85 and 60 Gy for the HR-CTV and the intermediate-risk CTV (IR-CTV) D90 (minimal dose received by 90% of the volume) in scenario 1, 90 and 60 Gy, respectively, for scenarios 2 and 3. For organs at risk, dose constraints were 90, 75 and 75 Gy to the bladder, rectum and sigmoid D2cm 3, respectively, in scenarios 1 and 2, and 80, 65 and 70 Gy in scenario 3. Results: A similar HR-CTV D90 could have been reached in scenarios 1 and 2 according to both pelvic doses. In scenario 3, a higher mean HR-CTV could have been reached in the 45 Gy arm (83.5 ± 8.0 versus 82.4 ± 8.0, P  < 0.0001). The mean D2cm 3 of organs at risk was systematically and significantly increased after a delivery of 50.4 Gy to the pelvis, from 0.9 to 2.89 Gy. The proportions of plans reaching planning aims were 85.8, 72.5 and 42.5% after 45 Gy and 85.5, 67.5 and 33.3% after 50.4 Gy according to scenarios 1, 2 and 3, respectively. According to scenario 3, 50.4 Gy, the reachable HR-CTV D90 was higher in 30% of the cases, by 2 Gy in two cases. Those cases were unpredictable and due to unfavourable organs at risk topography and poor response to external beam radiotherapy. Conclusion: The delivery of 45 Gy in 25 fractions to the pelvis before brachytherapy warrants a higher probability to reach brachytherapy planning aims, in comparison with 50.4 Gy in 28 fractions. Highlights: The treatment relies on a combination of EBRT and utero-vaginal brachytherapy (BT). 45 Gy in 25 fractions warrants a higher probability to reach BT planning aims. With the expected adoption of higher planning aims, this advantage will accelerate.